ANALISIS PENGGUNAAN ARTIFICIAL INTELLIGENCE (AI) DALAM AKTIVITAS SELF DIRECTED LEARNING (SDL) DAN KEMANDIRIAN AKADEMIK MAHASISWA DI FTIK UIN DATOKARAMA PALU - Muh. Aril Widi Saputra; Nurdin Nurdin; Andi Markarma; Hamka Hamka; Erniati Erniati (ACADEMIA: Jurnal Inovasi Riset Akademik, 2026)
ABSTRACT The rapid development of Artificial Intelligence (AI) has significantly transformed higher education, particularly in supporting self-directed learning (SDL) activities and the development of students’ academic independence. This study aims to analyze the use of AI in SDL activities and its implications for students’ academic independence at FTIK UIN Datokarama Palu. The research employed a mixed methods approach with a sequential exploratory design. The qualitative phase was conducted through in-depth interviews with 27 students from various study programs, while the quantitative phase involved distributing questionnaires to lecturers and academic administrators as stakeholders. Qualitative data were analyzed using thematic analysis, and quantitative data were analyzed using descriptive statistics. The findings indicate that AI is utilized by students as a tool for accessing academic information, assisting in task completion, supporting independent learning comprehension, and facilitating study planning. The use of AI also contributes to self-management, self-monitoring, and personal autonomy dimensions in SDL. Most lecturers responded positively to the integration of AI in students’ academic activities, although concerns remain regarding potential dependency and a decline in students’ critical thinking skills. This study concludes that AI plays a strategic role in supporting independent learning and students’ academic autonomy when used wisely, proportionally, and with an emphasis on developing critical thinking abilities.ABSTRAK Perkembangan Artificial Intelligence (AI) telah membawa perubahan signifikan dalam dunia pendidikan tinggi, khususnya dalam mendukung aktivitas self-directed learning (SDL) dan pembentukan kemandirian akademik mahasiswa. Penelitian ini bertujuan menganalisis penggunaan AI dalam aktivitas SDL serta implikasinya terhadap kemandirian akademik mahasiswa FTIK UIN Datokarama Palu. Penelitian menggunakan pendekatan mixed methods dengan desain sequential exploratory. Tahap kualitatif dilakukan melalui wawancara mendalam terhadap 27 mahasiswa dari berbagai program studi, sedangkan tahap kuantitatif dilakukan melalui penyebaran kuesioner kepada dosen dan pengelola akademik sebagai pemangku kepentingan. Data kualitatif dianalisis menggunakan thematic analysis dan data kuantitatif dianalisis dengan statistik deskriptif. Hasil penelitian menunjukkan bahwa AI dimanfaatkan mahasiswa sebagai sarana memperoleh informasi akademik, membantu penyelesaian tugas, mendukung pemahaman belajar mandiri, serta membantu perencanaan belajar. Pemanfaatan AI juga mendukung dimensi self-management, self-monitoring, dan personal autonomy dalam SDL. Mayoritas dosen memberikan respons positif terhadap penggunaan AI dalam aktivitas akademik mahasiswa, meskipun masih terdapat kekhawatiran terhadap potensi ketergantungan dan menurunnya daya kritis mahasiswa. Penelitian ini menyimpulkan bahwa AI memiliki peran strategis dalam mendukung pembelajaran mandiri dan kemandirian akademik mahasiswa apabila digunakan secara bijak, proporsional, dan berorientasi pada pengembangan kemampuan berpikir kritis.